A method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent

By using a combination of composite curing agents such as magnesium oxide and bentonite, the problem of contamination of various heavy metals in lead-zinc slag is solved, and the efficient curing and stabilization effect is achieved, which significantly reduces the environmental risks of heavy metals.

CN119100733BActive Publication Date: 2025-03-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411324057.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Heavy metals in lead-zinc slag are seriously polluted, and existing curing and stabilization technologies are difficult to effectively deal with the curing and stabilization of various heavy metals.

Method used

Using composite curing agents, including magnesium oxide and bentonite, magnesium oxide and biochar, bentonite and biochar, the curing and stabilization of heavy metals is achieved through uniform mixing and curing with lead-zinc slag powder.

Benefits of technology

The efficient curing and stabilization of four heavy metals, manganese, copper, zinc and lead in lead-zinc slag, has achieved high curing and stabilization rate of 88.50%~98.16%, and has reduced the mobility and biotoxicity of heavy metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119100733B_ABST
    Figure CN119100733B_ABST
Patent Text Reader

Abstract

The invention discloses a method for solidifying and stabilizing heavy metals in lead-zinc slag by using a composite solidifying agent. The method comprises: uniformly mixing a composite solidifying agent and water with lead-zinc slag powder and then curing the mixture to solidify and stabilize heavy metals in the lead-zinc slag, wherein the heavy metals include manganese, copper, zinc and lead; the composite solidifying agent is a composite solidifying agent A, a composite solidifying agent B or a composite solidifying agent C; the composite solidifying agent A contains magnesium oxide and bentonite, wherein the mass ratio of magnesium oxide to bentonite is 2:1-4; the composite solidifying agent B contains bentonite and biochar, wherein the mass ratio of bentonite to biochar is 2:1-4; the composite solidifying agent C contains magnesium oxide and biochar, wherein the mass ratio of magnesium oxide to biochar is 2:1-4; and the mass ratio of the composite solidifying agent to the lead-zinc slag powder is 5-20:100.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of harmless treatment of solid wastes, and in particular to a method for solidifying and stabilizing heavy metals in lead-zinc slag by using a composite solidifying agent. Background Art

[0002] With the intensified development of human activities such as smelting, mining, agriculture, and leather making, the problem of heavy metal pollution has become more and more serious, including major problems such as heavy metal pollution in the water environment and heavy metal pollution in the soil, which is directly related to agricultural production, food safety, human health, and the sustainable development of the ecological environment.

[0003] The amount of lead and zinc mining and consumption in the world is increasing year by year. However, due to the limitation of technology level, the mining process often leads to heavy metal pollution in the surrounding environment. A large amount of lead and zinc slag is difficult to use and will enter the soil and surrounding groundwater environment with rainwater leaching, causing serious heavy metal pollution of water and soil. Lead and zinc heavy metals can cause serious impacts on the human nervous system, digestive system, and respiratory system, so it is urgent to deal with the problem of heavy metal pollution in lead and zinc slag.

[0004] The most commonly used and effective method is solidification stabilization technology. Solidification stabilization technology refers to adding a solidifying agent to the pollutant to change its physical and chemical properties, generate some difficult-to-degrade products with heavy metals to reduce the mobility of heavy metals, fix them in the pollutant, and thus reduce environmental risks.

[0005] The patent specification with publication number CN114276055A discloses a heavy metal solidification stabilizer for tailings treatment and its application. The heavy metal solidification stabilizer is composed of active silicon solid waste and calcium-rich solid waste, and its Ca / Si weight ratio is 1:1~3:1; wherein the active silicon solid waste is at least one of slag, active silica, and rice husk ash; and the calcium-rich solid waste is industrial waste gypsum or quicklime. The patented technology prepares the heavy metal solidification stabilizer, tailings, and water into a slurry, and solidifies the slurry to fix heavy metals such as lead, cadmium, and chromium in the lead-zinc tailings, so that the heavy metal stabilization rate of the tailings is greater than 99%.

[0006] The patent specification with the publication number CN113387669A discloses a red mud-phosphogypsum-based heavy metal curing agent, its preparation method and application. The red mud-phosphogypsum-based heavy metal curing agent includes the following components by weight: 70-80 parts of red mud-phosphogypsum mixture, 20-30 parts of water-quenched alkaline ferrocene slag, and 1-10 parts of admixture; wherein the mass ratio of red mud to phosphogypsum in the red mud-phosphogypsum mixture is 1:(0.25-4.5). The red mud-phosphogypsum-based heavy metal curing agent of the patented technology has a high dosage of red mud-phosphogypsum, which reduces the environmental pollution caused by the storage of red mud and phosphogypsum; it can replace cement and reduce the cost of tailings curing and stabilization; it has a good curing and stabilizing effect on lead-zinc tailings, and improves the stability and safety of the heavy metal tailings pond by increasing the mechanical strength of the cured tailings. Summary of the invention

[0007] In a first aspect, the present invention provides a method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent, comprising: mixing a uniform mixture of a composite curing agent and water with lead-zinc slag powder and then curing to cure the heavy metals in the lead-zinc slag, wherein the heavy metals include manganese, copper, zinc and lead;

[0008] The composite curing agent is composite curing agent A, composite curing agent B or composite curing agent C;

[0009] The composite curing agent A contains magnesium oxide and bentonite, wherein the mass ratio of magnesium oxide to bentonite is 2:1-4;

[0010] The composite curing agent B contains bentonite and biochar, wherein the mass ratio of bentonite to biochar is 2:1-4;

[0011] The composite curing agent C contains magnesium oxide and biochar, wherein the mass ratio of magnesium oxide to biochar is 2:1-4;

[0012] The mass ratio of the composite curing agent to the lead-zinc slag powder is 5 to 20:100, for example, 10:100, 15:100, etc.

[0013] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent as described in the first aspect, the particle size of the lead-zinc slag powder is preferably less than 120 mesh.

[0014] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent described in the first aspect, the curing conditions preferably include: a curing temperature of 20 to 30°C, such as 25°C, a relative humidity of the curing environment of more than 90%, and a curing time of 3 to 28 days, such as 7 days, 14 days, etc.

[0015] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent described in the first aspect, the biochar can be obtained by sintering municipal sludge at 690-710° C. (eg, 700° C.) in a nitrogen atmosphere.

[0016] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent as described in the first aspect, the particle size of the biochar is preferably less than 200 mesh.

[0017] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent described in the first aspect, the mass ratio of the water to the lead-zinc slag powder can be 5 to 15:100, for example, 1:10.

[0018] In the method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent described in the first aspect, the composite curing agent preferably contains magnesium oxide and bentonite in a mass ratio of 1:1.

[0019] In a second aspect, the present invention provides an application of a composite curing agent for curing and stabilizing heavy metals in lead-zinc slag, wherein the heavy metals include manganese, copper, zinc and lead;

[0020] The composite curing agent is composite curing agent A, composite curing agent B or composite curing agent C;

[0021] The composite curing agent A contains magnesium oxide and bentonite, wherein the mass ratio of magnesium oxide to bentonite is 2:1-4;

[0022] The composite curing agent B contains bentonite and biochar, wherein the mass ratio of bentonite to biochar is 2:1-4;

[0023] The composite curing agent C contains magnesium oxide and biochar, wherein the mass ratio of magnesium oxide to biochar is 2:1-4.

[0024] The application described in the second aspect can refer to the method described in the first aspect for specific selection and optimization of technical solutions.

[0025] In some embodiments, the application described in the second aspect may specifically include: mixing a uniform mixture of a composite curing agent and water with lead-zinc slag powder and then curing to solidify and stabilize heavy metals in the lead-zinc slag. Furthermore, the mass ratio of the composite curing agent to the lead-zinc slag powder may be 5 to 20:100, such as 10:100, 15:100, etc. The mass ratio of the water to the lead-zinc slag powder may be 5 to 15:100, such as 1:10, etc. The curing conditions may include: a curing temperature of 20 to 30°C, such as 25°C, a relative humidity of the curing environment of more than 90%, and a curing time of 3 to 28 days, such as 7 days, 14 days, etc.

[0026] In the application described in the second aspect, the composite curing agent preferably contains magnesium oxide and bentonite in a mass ratio of 1:1.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The invention adopts a specific composite curing agent, which can simultaneously cure and stabilize four heavy metals, namely manganese, copper, zinc and lead, in the lead-zinc slag at one time, has high curing and stabilization efficiency, a simple formula of the composite curing agent, low cost, convenient curing operation, and is suitable for industrial application.

[0029] When a composite curing agent containing magnesium oxide and bentonite is used to solidify and stabilize heavy metals such as manganese, copper, zinc and lead in lead-zinc slag, brucite with a lamellar structure and hydrated calcium silicate with a needle-rod structure will be newly generated in the solidified and stabilized lead-zinc slag product. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Heavy metal leaching concentrations of slag treated with different solidifying agents at 10% addition: (a) manganese, (b) copper, (c) zinc, and (d) lead.

[0031] Figure 2 Heavy metal leaching concentrations of slag treated with different proportions of MgB at an addition rate of 15%: (a) manganese, (b) copper, (c) zinc, and (d) lead.

[0032] Figure 3 The results of the analysis of the changes in the forms of four heavy metals, manganese, copper, lead and zinc, in the slag treated with 15% addition of Mg1B1 curing agent: (a) manganese, (b) copper, (c) lead and (d) zinc. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0034] Unless otherwise specified, the following experimental process uses the following method to solidify and stabilize heavy metals in lead-zinc slag, specifically including: mixing a uniform mixture of composite curing agent and water with lead-zinc slag powder with a particle size of less than 120 mesh and then curing to solidify and stabilize heavy metals in lead-zinc slag. Among them, the mass ratio of water to lead-zinc slag powder (liquid-to-solid ratio) is 1:10, and the curing conditions include: the curing temperature is 25°C, the relative humidity of the curing environment is 90%, and the curing time is 3 to 28 days.

[0035] The biochar used in the embodiment is obtained by calcining municipal sludge at 700° C. in a nitrogen atmosphere, and the particle size is less than 200 meshes.

[0036] The present invention studies the effect of composite curing agent on the curing of four heavy metals in slag, namely manganese (Mn), copper (Cu), zinc (Zn) and lead (Pb). Three types of composite curing agents, MgB (magnesium oxide bentonite composite curing agent), MgC (magnesium oxide biochar composite curing agent) and BC (bentonite biochar composite curing agent), were designed in the experiment, and the best curing agent type, doping ratio and optimal addition amount (the addition amount refers to the mass ratio of the composite curing agent and the lead-zinc slag powder, which will not be explained again below) were explored through curing and stabilization experiments. In the experiment, samples were taken after 3 days, 7 days, 14 days and 28 days of curing agent treatment on the slag, and ICP-MS was used to detect the leaching concentration of heavy metals in the lead-zinc slag. The solidification rate W of heavy metals was calculated using the following formula: W=(C0-C1) / C0×100%. Specifically, the solidification rate W is defined as the ratio of the difference between the leaching concentration C1 of the four heavy metals (Mn, Cu, Zn, Pb) after the lead-zinc slag was treated with the curing agent for the corresponding number of days and the leaching concentration C0 of the untreated slag to the leaching concentration C0 of the untreated slag.

[0037] The detailed experimental design is shown in Table 1 , where Mg represents magnesium oxide, B represents bentonite, and C represents municipal sludge biochar.

[0038] Table 1

[0039]

[0040] When the composite curing agent was added at a rate of 10%, any two of the three curing agents, magnesium oxide, bentonite, and municipal sludge biochar, were selected and mixed in a mass ratio of 1:1, namely magnesium oxide bentonite composite curing agent (Mg1B1), magnesium oxide biochar composite curing agent (Mg1C1), and bentonite biochar composite curing agent (B1C1). The leaching concentrations of four heavy metals, Mn, Cu, Zn, and Pb in lead-zinc slag were detected on the 3rd, 7th, 14th, and 28th days, respectively. Magnesium oxide (Mg), bentonite (B), and municipal sludge biochar (C) were used alone (10% addition) as the control group to compare with the effect of the composite curing agent. The solidification and stabilization effects of several curing agents on the four heavy metals, manganese, copper, zinc, and lead, are shown in Figure 2. Figure 1 shown.

[0041] Figure 1(a), (b), (c), and (d) are the leaching concentrations of four heavy metals, manganese, copper, lead, and zinc, on the 3rd, 7th, 14th, and 28th days, respectively. It can be clearly seen that for the four heavy metals, the heavy metal concentration of the slag treated with B1C1 (bentonite biochar composite solidifier) ​​at a 10% addition amount is the highest, and the solidification effect is the worst, followed by the slag treated with B (bentonite solidifier) ​​and C (biochar solidifier) ​​used alone. The main reason is that bentonite mainly solidifies and stabilizes heavy metals through adsorption, and its adsorption capacity for different heavy metals is also different. For example, the heavy metal with better adsorption effect is cadmium (Cd), but the adsorption effect on manganese, copper, lead, and zinc in lead-zinc slag is average. Biochar relies on its high specific surface area, large porosity and surface functional groups to adsorb and fix heavy metals, so its adsorption capacity for heavy metals is limited. In addition, the optimal pH range for biochar as a curing agent to treat heavy metals is 5~9, while the pH of lead-zinc slag is much higher than this range, which inhibits the curing performance of biochar. On the 14th day, magnesium oxide had the best heavy metal curing effect, but the heavy metal leaching concentration often showed an upward trend afterwards, indicating that its curing effect was unstable. The main reason is that magnesium hydroxide mainly forms hydroxide complexes by increasing the pH, but with the consumption of hydroxide, the pH decreases, resulting in an increase in the solubility of some hydroxides, which leads to a rebound in the heavy metal leaching concentration. The two composite curing agents containing magnesium oxide, Mg1B1 and Mg1C1, showed an upward trend in the heavy metal leaching concentrations of the slag treated on the 28th day. The slag treated with Mg1C1 had an upward trend in the heavy metal leaching concentrations of Mg1B1 and Mg1C1. The increase in heavy metal leaching concentration is more obvious. Taking the 28-day heavy metal leaching effect as the standard, the Mg1B1 composite curing agent has the best curing effect, and the leaching concentration on the 28th day is lower than the leaching concentration of magnesium oxide alone. This shows that compared with the use of each alone, the combination of magnesium oxide and bentonite has a significant synergistic effect on the solidification and stabilization of four heavy metals, manganese, copper, zinc and lead in lead-zinc slag. The curing rates of the four heavy metals Mn, Cu, Zn and Pb are 88.50%, 67.55%, 93.67% and 90.66%, respectively.

[0042] In previous studies, it was determined that the solidification and stabilization effect of the composite curing agent on the four heavy metals Mn, Cu, Zn, and Pb in lead-zinc slag is completely superior to the effect of the three traditional curing agents used alone, and it can treat multiple heavy metals at the same time, which is of great significance for multi-metal pollution in the actual remediation process. On the basis of determining that the combined use of magnesium oxide and bentonite has a better effect, different mixing ratios of the two were used to explore their effects on the solidification and stabilization of the four heavy metals manganese, copper, lead, and zinc in lead-zinc slag. At an addition amount of 15% of the composite curing agent, magnesium oxide and bentonite were added in three mass ratios of 2:1, 1:1, and 1:2 to prepare composite curing agents to treat lead-zinc slag. The effects of the magnesium oxide bentonite composite curing agent at the three ratios on the leaching concentrations of the four heavy metals Mn, Cu, Zn, and Pb are shown as follows: Figure 2 shown.

[0043] from Figure 2 It can be seen that when the mass ratio of magnesium oxide to bentonite is 1:1, the leaching concentrations of heavy metals Mn, Cu, Zn and Pb in the slag treated with the composite curing agent Mg1B1 at an addition of 15% on the 28th day are the lowest, and the curing effect is the best. The 28-day curing rates of the four heavy metals manganese, copper, lead and zinc are 96.54%, 70.43%, 94.04% and 98.16%, respectively. Moreover, the curing effect on the four heavy metals is most obvious in the first 14 days, and it begins to slowly recover after the 14th day. However, when the mixing ratio of magnesium oxide and bentonite is 1:1, the 28-day curing rates of the four heavy metals are The rebound amplitude of heavy metal leaching concentration is the smallest, indicating that at a ratio of 1:1, the stability of heavy metal solidification and stabilization by MgB solidifier is better, and the mixed use with bentonite improves the stability and long-term validity of heavy metal solidification and stabilization by magnesium oxide. Due to the high specific area of ​​bentonite, it plays a more load-bearing role in the solidification and stabilization process, improves the solidification rate of magnesium oxide, thereby reducing the leaching of heavy metals, and through its own layered structure, it plays a fixing role on magnesium hydroxide, magnesium carbonate and other hydration products produced by magnesium oxide and heavy metal ions in water environment, thereby enhancing the stability of the solidification effect. The results show that magnesium oxide and bentonite have a good synergistic effect in the process of heavy metal solidification and stabilization, and can effectively deal with the problem of compound pollution of multiple heavy metals such as manganese, copper, lead and zinc.

[0044] Under the condition that the best composite curing agent type is Mg1B1, this study set four addition amount gradients of 5%, 10%, 15%, and 20% to explore the best Mg1B1 curing agent addition amount when treating lead-zinc slag. The results of the curing agent under the four gradients on the leaching concentration of four heavy metals of manganese, copper, lead and zinc in lead-zinc slag showed that within the range of 5% to 15%, the leaching concentration of all four heavy metals decreased with the increase of the addition amount of curing agent, indicating that between 5% and 15%, by increasing the addition amount of curing agent, the leaching concentration of four heavy metals Mn, Cu, Zn and Pb can be effectively reduced. , effectively improving the solidification rate of the four heavy metals. However, when the addition amount of the curing agent reaches 20%, compared with the addition amount of 15%, the heavy metal leaching concentration at 20% addition has no obvious change compared with the heavy metal leaching concentration at 15% addition, and the leaching concentration curves basically overlap, indicating that increasing the addition amount of the curing agent on the basis of 15% addition has little effect on the solidification rate of the four heavy metals. At 15% addition, the curing agent has reached saturation for the solidification and stabilization of the four heavy metals. Considering the feasibility of economic benefits in the actual implementation process, 15% addition of Mg1B1 curing agent is already the best choice.

[0045] Scanning electron microscopy, X-ray diffraction and other techniques were used to investigate the composition changes and microstructural changes of lead-zinc slag after heavy metal solidification and stabilization of lead-zinc slag by adding 15% Mg1B1 curing agent. The results showed that lamellar brucite and needle-rod-like hydrated calcium silicate were produced in the Mg1B1-treated slag.

[0046] The BCR heavy metal form analysis method was used to investigate the effect of the Mg1B1 composite curing agent on the form of heavy metals. The heavy metal forms were divided into four forms: (F1) weakly acid extractable state, (F2) oxidizable state, (F3) reducible state, and (F4) residual state. Heavy metals in the first three valence states are more easily absorbed by plants or affected by microbial activities, so their environmental risks are relatively high. Heavy metals in the residual state are relatively stable and not easily utilized or migrated by organisms.

[0047] The slag samples treated with 15% Mg1B1 curing agent were sampled and tested on the 3rd, 7th, 14th and 28th days respectively. The untreated slag (raw material) was used as the blank control group to analyze the changes in the forms of four heavy metals: manganese, copper, lead and zinc. The specific results are as follows: Figure 3As shown, it can be clearly seen that for any heavy metal of manganese, copper, lead and zinc, the proportion of its weak acid extractable state in the original slag is basically the highest, except that the oxidizable state of heavy metal lead has the highest content, accounting for 36%. Secondly, there is no obvious difference in the proportion of oxidizable state and reducible state among heavy metals Mn, Cu, Zn and Pb. At the same time, the proportion of the four heavy metals Mn, Cu, Zn and Pb in the residual state is the lowest, accounting for 9%, 13%, 12% and 14% respectively, reflecting that the mobility of heavy metals in the original slag is high and the biological toxicity is stronger. In addition, it can be clearly seen that the curing effect of Mg1B1 curing agent on these four heavy metals basically reaches stability on the 14th day, especially for the curing effect of heavy metals manganese and copper. There is no obvious difference between the 7th day and the 14th day. This may be because the raw material used is lead-zinc slag. Compared with heavy metals lead and zinc, the content of heavy metals manganese and copper is lower, and the best effect can be achieved in a short time. During the solidification and stabilization process of heavy metal manganese, the contents of weak acid extractable, oxidizable and reducible forms of manganese showed a downward trend overall, while the residual form showed an upward trend overall, increasing from 9% in the raw materials to 23%, indicating that the curing agent can effectively convert other forms of heavy metal manganese into a residual form with lower mobility and less biological toxicity. The morphological changes of heavy metal copper during the solidification process are basically consistent with those of heavy metal manganese. As for heavy metals lead and zinc, from Figure 3 It can be clearly seen that on the 28th day, the residual state content of the two is still rising, increasing from 12% to 30% and 14% to 38%, respectively, which are 2.5 and 2.7 times of the untreated slag, but it can be seen that the growth rate of the residual state gradually decreases with the extension of time. These phenomena indicate that the solidification and stabilization of heavy metals by Mg1B1 curing agent is mainly concentrated in the first 14 days, and then gradually slows down. Due to the slow consumption of the curing agent, the curing rate slowly decreases. The above results show that the addition of Mg1B1 composite curing agent can promote the transformation of heavy metal forms from weakly acid extractable, oxidizable, and reducible states to residual states with lower mobility and weaker biological toxicity, thereby improving the solidification rate of heavy metals, especially for heavy metals zinc and lead. The residual states of the two increased to 2.5 and 2.7 times of the untreated slag on the 28th day.

[0048] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for curing and stabilizing heavy metals in lead-zinc slag using a composite curing agent, characterized in that: include: The uniform mixture of the composite curing agent and water is mixed with the lead-zinc slag powder and then cured to solidify and stabilize the heavy metals in the lead-zinc slag, wherein the heavy metals include manganese, copper, zinc and lead; The composite curing agent contains magnesium oxide and bentonite in a mass ratio of 1:1; The mass ratio of the composite curing agent to the lead-zinc slag powder is 15-20:100; After solidification and stabilization, brucite with a lamellar structure and hydrated calcium silicate with a needle-rod structure are newly generated in the lead-zinc slag product.

2. The method according to claim 1, characterized in that: The particle size of the lead-zinc slag powder is less than 120 meshes.

3. The method according to claim 1, characterized in that The curing conditions include: a curing temperature of 20 to 30° C., a relative humidity of the curing environment of more than 90%, and a curing time of 3 to 28 days.

4. The method according to claim 1, characterized in that The mass ratio of the water to the lead-zinc slag powder is 5 to 15:

100.

5. A composite curing agent for curing and stabilizing heavy metals in lead-zinc slag, characterized in that: The heavy metals include manganese, copper, zinc and lead; The application specifically includes: mixing a uniform mixture of a composite curing agent and water with lead-zinc slag powder and then curing to solidify and stabilize heavy metals in the lead-zinc slag; The composite curing agent contains magnesium oxide and bentonite in a mass ratio of 1:1; The mass ratio of the composite curing agent to the lead-zinc slag powder is 15-20:100; After solidification and stabilization, brucite with a lamellar structure and hydrated calcium silicate with a needle-rod structure are newly generated in the lead-zinc slag product.

6. The use according to claim 5, characterized in that: The mass ratio of the water to the lead-zinc slag powder is 5 to 15:

100.

7. The use according to claim 5, characterized in that: The curing conditions include: a curing temperature of 20 to 30° C., a relative humidity of the curing environment of more than 90%, and a curing time of 3 to 28 days.

Citation Information

Patent Citations

  • Red mud-ardealite-based heavy metal curing agent, and preparation method and application thereof

    CN113387669A

  • Heavy metal curing stabilizer for tailing treatment and application of heavy metal curing stabilizer

    CN114276055A

  • Heavy metal contaminated soil composite remediation agent and using method and application thereof

    CN110252798A

  • Long-acting evaluation method for active magnesium oxide solidified / stabilized zinc-containing smelting slag based on carbonation accelerated exposure

    CN114428149A